2020
DOI: 10.1101/2020.04.15.043315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward a Connectivity Gradient-Based Framework for Reproducible Biomarker Discovery

Abstract: Despite myriad demonstrations of feasibility, the high dimensionality of fMRI data remains a critical barrier to its utility for reproducible biomarker discovery. Recent studies applying dimensionality reduction techniques to resting-state fMRI (R-fMRI) have unveiled neurocognitively meaningful connectivity gradients that are present in both human and primate brains, and appear to differ meaningfully among individuals and clinical populations. Here, we provide a critical assessment of the suitability of connec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Next, to investigate changes in cortical and subcortical patterns of functional connectivity during SL, we used the centered matrices to estimate separate cortical-subcortical connectivity manifolds for each participant's Pre-learning, Early-learning, Late-learning, and Post-learning covariance matrices. Building from prior work (36,(59)(60), we converted each centered connectivity matrix into an affinity matrix before applying PCA to the entire sample's affinity matrices. This reveals a set of principal components (PCs), which offer a low-dimensional representation of the cortical and subcortical structure (i.e., a cortical-subcortical manifold).…”
Section: Investigating Changes In Functional Brain Organization Durin...mentioning
confidence: 99%
“…Next, to investigate changes in cortical and subcortical patterns of functional connectivity during SL, we used the centered matrices to estimate separate cortical-subcortical connectivity manifolds for each participant's Pre-learning, Early-learning, Late-learning, and Post-learning covariance matrices. Building from prior work (36,(59)(60), we converted each centered connectivity matrix into an affinity matrix before applying PCA to the entire sample's affinity matrices. This reveals a set of principal components (PCs), which offer a low-dimensional representation of the cortical and subcortical structure (i.e., a cortical-subcortical manifold).…”
Section: Investigating Changes In Functional Brain Organization Durin...mentioning
confidence: 99%
“…The dimensionality reduction techniques applied here are particularly suitable, as they provide an intrinsic and continuous coordinate system that situates individual regions within the global landscape of the cortical connectome. Gradients in our sample of middle old healthy individuals who underwent extensive screening before study enrollment (Singer et al, 2016), recapitulated prior work in healthy young adults (Hong et al, 2020;Margulies et al, 2016). Indeed, in accordance to prior studies, we observed that G1 traversed a sensory-fugal axis, running from unimodal to transmodal systems such as the default mode and fronto-parietal networks.…”
Section: Discussionsupporting
confidence: 87%
“…Such large-scale functional gradients can be reliably identified from in vivo functional connectivity information, by applying techniques that identify principal dimensions of connectivity variations from one region to the next. As such, they provide a low-dimensional coordinate system reflecting macroscale neural organization, specifically accounting for both functional segregation across regions as well as their integration (Haak and Beckmann, 2020;Haak et al, 2018;Hong et al, 2020;Margulies et al, 2016;Shine et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning fMRI acquisition, previous studies have shown that many non-neural factors may influence the variation in fMRI signals and, consequently, the reliability of the intra- and inter-individual FC ( Hong et al, 2020 , Birn et al, 2008 ). One example is scanning duration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, four studies used global signal regression for physiological motion correction, which is a risk of discarding global neural information ( Power et al, 2014 , Murphy and Fox, 2017 ). Recent work explored a set of benchmark parameters for the use of FC as a tool in the domain of biomarker discovery including: using a linear dimensionality reduction algorithm, utilizing the gradients that explain a greater amount of the variance of the data and extracting gradients using more conservatively threshold FC matrices ( Hong et al, 2020 ). Future work in this direction and exploration of large-sample test–retest neuroimaging datasets, will be valuable in biomarker development and may impact the interpretation of findings summarized in this review.…”
Section: Discussionmentioning
confidence: 99%